Perlindungan Hukum terhadap Perempuan Kepala Keluarga di Desa Studi Kasus Kebijakan BLT dan Akses Ekonomi Dijawa Tengah - Usman, Arya Ramadhan; Mokodogan, Natasya; Moonti, Roy Marthen (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Female-headed households (PEKKA) in rural areas represent a vulnerable group that often faces structural barriers in accessing their social and economic rights, particularly in relation to Cash Transfer Assistance (BLT) policies. The urgency of this study stems from the persistent gap between policy implementation and the specific needs of PEKKA. This research aims to examine the forms of legal protection and economic access available to PEKKA in several villages in Central Java through the BLT scheme. Utilizing a qualitative approach, data were collected through in-depth interviews, observation, and document analysis, and analyzed using descriptive qualitative methods. The findings reveal that administrative obstacles, social stigma, and the lack of gender-sensitive approaches are key factors hindering the fulfillment of PEKKA’s rights. Although formal policies exist, their implementation at the local level remains unresponsive and fails to address structural inequalities. This study contributes to the development of socially just and gender-equitable policy frameworks at the village level. It concludes that reformulating inclusive and advocacy-based social policies for PEKKA is essential, alongside further research exploring transformative legal approaches and sustainable economic empowerment.